Aggressive Helicobacter pylori-negative peptic ulceration as the initial manifestation of Crohn's disease. Issue 3 (1st May 2012) - Callaghan, James; Brown, Sarah; Battcock, Tim; Parry, Sally; Snook, Jonathon
Abstract : Peptic ulceration is a recognised feature of Crohn's disease, but the characteristics of this manifestation are rather poorly described. Furthermore, most reports in the literature relate to ulcer disease in cases of established Crohn's disease. The authors report a series of four cases in which the diagnosis of Crohn's disease was preceded by peptic ulceration. Potential confounding factors were as far as possible excluded, implying a true association. Characteristics of the ulcer disease included (1) a multifocal distribution, (2) Helicobacter pylori negativity and (3) an unusually aggressive clinical course despite proton pump inhibitor therapy, necessitating endoscopic or surgical intervention in three cases. Crohn's-related peptic ulceration is a relatively common manifestation which may precede the diagnosis of Crohn's disease itself. Recognition of the underlying diagnosis may be hampered by non-specific histology, but is important in view of the aggressive course of the ulceration, which may respond to medical therapy for Crohn's disease.